2018
DOI: 10.21037/jtd.2018.02.16
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the relationship between baseline lactate dehydrogenase and prognosis in patients with extensive-disease small cell lung cancer: a retrospective cohort study

Abstract: Background: Elevated pretreatment lactate dehydrogenase (LDH) has been reported to be associated with poor survival in small cell lung cancer (SCLC). The present study aimed to investigate the continuous relationship between baseline LDH level and survival in patients with extensive-disease SCLC (ED-SCLC). Results: A total of 132 eligible ED-SCLC patients were analyzed. Elevated LDH at baseline was associated with poor survival (HR =1.92; 95% CI,). An increment of LDH would still raise the risk of death even i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Sixty percent had brain-only metastases. We found that elevated LDH was associated with significantly shorter survival, in line with our previous results in a larger study of patients who mainly had non-in vivo 33: 229-232 (2019) oligometastatic brain metastases (13) and with other studies in different settings (15)(16)(17).…”
Section: Discussionsupporting
confidence: 92%
“…Sixty percent had brain-only metastases. We found that elevated LDH was associated with significantly shorter survival, in line with our previous results in a larger study of patients who mainly had non-in vivo 33: 229-232 (2019) oligometastatic brain metastases (13) and with other studies in different settings (15)(16)(17).…”
Section: Discussionsupporting
confidence: 92%
“…20 Some researchers believe that LDH is an independent prognostic factor of lung cancer and is closely related to the TNM stage, therapeutic effect and survival of lung cancer. 21 , 22 Additionally, serum LDH levels can be used as prognostic indicators for malignant tumors such as colorectal cancer, 23 nasopharyngeal carcinoma, 24 prostate cancer 25 and breast cancer. 26 Our study showed that LDH >132 IU/L was associated with better prognosis in LSCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one of the first major breakthroughs in cancer research was the discovery that tumor cells are biased towards aerobic glycolysis rather than oxidative phosphorylation to produce energy (i.e., the Warburg effect [95][96][97] ). Therefore, a common finding in malignant cancers is a strong upregulation of lactate and catalytic enzymes required for lactate production from pyruvate (e.g., lactate dehydrogenase) [98][99][100][101] . Lactate normally acts to aide in glucose sensing and food intake, where it is transported into the brain via monocarboxylate transporters present on endothelial cells lining the blood-brain barrier [102] .…”
Section: Energy Balance and Feedingmentioning
confidence: 99%